Dermatology in Primary Care in Brazil: The training process of general practitioners (Research, Society and Development, 2024)
Dermatological diseases are a common complaint in healthcare services in Brazil, especially in primary care. Therefore, it is crucial for general practitioners to possess the ability to diagnose and treat these conditions appropriately, aiming to minimize the impact on the quality of life of their patients. However, several obstacles hinder the performance of these professionals in dermatology, directly affecting the diagnosis and treatment of skin disorders in primary care. Given this scenario, a thorough analysis of key structural issues was conducted, with an emphasis on the doctor-patient dynamic and the training of physicians in primary care. The study underscored the need for in-depth investigation during undergraduate education and in the remnants of the post-colonial period, with the purpose of establishing concepts based on medical education issues and structural challenges related to Brazil's historical-economic development.